SISTEM INFORMASI MONITORING PRESTASI AKADEMIK DI SDN GADINGREJO I BERBASIS WEB - Sigit Riyadi; Siska Anggraeni (STMIK YADIKA BANGIL, 2016)
Abstract: Value is one important component in teaching and learning activities in schools that will be input into output is expected to be offset even develop each student's grades . in this paper will explaint a metode a aplication system to able handle it .Web -based information using assistive technologies such as PHP and the MySQL databaseto provide convenience for the admin in this case the class teacher teachers and students to access through any device over the network connected to the Internet . using admin of processing the value that can be processed effectively and efficiently .Keywords:Monitoring, Webaplcation,